Implemetasi Pada Guru/Pegawai di SMA Negeri 12 Pekanbaru Dengan Metode Tes Uji Rinne Pada Remaja Gangguan Pendengaran Dengan Penggunaan Handphone - Chairil; Ratih Oktaviani (Sistem Informasi, 2020)
Mobile phone is one of the developing communication tools today. The global debate and controversy regarding the health effects of cell phones continues. There are concerns that radio frequency energy (radio waves) emitted can cause health problems, especially to hearing function. The aim of the study was to find out how "the description of hearing loss with the use of mobile phones in Pekanbaru 12 SMA. The type of research used is descriptive with probality sampling sampling technique where the sample in this study is to take respondents based on random or coincidental in SMA Negeri 12 Pekanbaru which amounted to 249 respondents. Data collection tools using questionnaires as well as examination of auditory function by means of the rinne test used is univariate. The results of the research which was conducted on 23 July - 28 July 2018 showed that of 249 respondents (100%) were all mobile users and from the results of rinne test, 66 respondents (26.5%) had positive hearing loss and 183 respondents (73 , 5%) negative did not experience hearing loss.